Roles of Test-taking Strategies, Self-regulation Strategies, and Self-efficacy in Iranian Ph.D. Candidates’ Language Proficiency - Rahimi Esfahani, Fariba; Shafiee, Sajad (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The purpose of this study was to examine the roles that self-efficacy, self-regulation strategies, and test-taking strategies could play in the language proficiency scores of the PhD candidates at Islamic Azad University (IAU). Nighty-eight students were recruited from a range of disciplines at the Ph.D. level at IAU, Shahrekord Branch, Shahrekord, Iran. They were asked to fill out the Self-efficacy, Self-regulation Strategies, and Test-taking Strategies Questionnaires . They were also given an EPT sample test as their final exam for the English course they were taking. The results of Multiple regression analysis showed that language proficiency was strongly, positively, and significantly correlated with self-regulation, test-taking strategies, and self-efficacy. These results suggest that individual attributes such as self-regulation and self-efficacy as well as test-wiseness play a major part in the success of students in language proficiency tests.